DOCTRINE OF CAUSALITY AND PROOF OF CRIMINAL ACTIONS IN THE JESSICA WONGSO CYANIDE COFFEE CASE - Zaeni Aji Bakhtiar; Hadi Purnomo (Riviera Publishing, 2024)
Criminal law is a sub-section of law that creates peace and order in society, because the existence of criminal law in society cannot be separated from the state's efforts to create order. To determine the penalty for a criminal act, it is necessary to pay attention to the doctrine of cause and effect and evidence of the occurrence of the criminal act. For this reason, the aim of this research is to analyze the teachings of causality and evidence of the crime in the cyanide coffee case committed by the defendant Jessica Wongso against the victim Wayan Mirna Salihin in 2016. This research uses qualitative research methods. The data collection technique in this research uses the literature study method. The data that has been collected is then analyzed through three stages, namely data reduction, data presentation, and drawing conclusions. The research results show that the doctrine of causality is very important because it relates to which actions should be considered as the cause of prohibited effects. The judge assessed that Jessica's actions, namely putting cyanide poison in the coffee that Mirna drank, were the direct cause of Mirna's death. This decision was based on several considerations, namely the discovery of cyanide poison in Mirna's coffee, no one else had put cyanide poison in Mirna's coffee, and the defendant had a motive to kill the victim. In this case, the judge relied on witness testimony, expert testimony and evidence to prove Jessica's crime. Based on the teachings of causality and evidence, the judge sentenced Jessica as the defendant to 20 years in prison. This circumstantial evidence has given rise to much controversy. However, despite the controversy, the coffee cyanide case shows the importance of the teachings of causality and evidence of criminal acts in criminal law.